Korean war June-October 1950 : Inchon and Stalin in the "trigger vs. justification" debate - Tan, Jack Kwoh (2009)
China's decision to enter the Korean War in 1950 is a historical puzzle: why would China, a much weaker country, enter into a military confrontation with the United Korea carries strategic lessons for the contemporary crisis on the Korean Peninsula, as well as for Sino-American relations. Utilizing newly declassified Russian documents made available at the Cold War International History Project from 1994-2004, this paper critically assesses this new evidence concurrently with the existing literature that has emerged so far, and seeks to contribute to the "trigger vs. justification" debate surrounding China's entry. Three shortcomings of this debate are identified: 1) whether Mao would have intervened had the US military stopped at the 38th parallel is difficult to determine; 2) Mao's vacillations up till the very last minute cast doubt on the justification arguement i.e. offensive intervention driven by revolutionary ideology and politics; and 3) as a result, this ignores the complex dimensions of decision-making and interaction between Stalin and the Chinese leadership, as well as within the Chinese leadership itself. This paper argues that one significant variable overlooked heretofore is the American landings at Inchon on 19 September 1950. This is followed by in-depth analyses of the following three main interactions that Inchon engendered - 1) the policy shifts within the Truman administration; 2) the Stalin-Mao manoeuvres; and 3) the debates and dilemmas within the Chinese Politburo. This paper concludes that it was Inchon, along with additional pressure from Stalin, and not the crossing of the 38th parallel, that triggered China's eventual entry into Korea.